Characterization of Surface Active Shell Charcoal Nyamplung Seeds (Calophyllum inophyllum Linn) - Wibowo, Santiyo; Syafi, Wasrin; Pari, Gustan (Makara Journal of Technology, 2011)
Characterization of Surface Active Shell Charcoal Nyamplung Seeds (Calophyllum inophyllum Linn). Chemical and physical activation of nyamplung shell with 0%, 5%, and 10% H3PO4 for 60 and 120 minutes has been carried out to prepare activated charcoal. The purpose of this experiment was to look into the characteristic of nyamplung shell activated charcoal surface. Nyamplung shell was carbonized into charcoal, then activated by immersion in H3PO4 solution using 0%, 5% and 10%, for 24 hours, and heated in retort at two temperatures (700 and 800 oC) and two duration (60 and 120 minutes). The material were characterized by fourier transform infra red (FTIR), scaning electron microscope (SEM) and X-ray diffraction (XRD). The FTIR spectrum show that activated charcoal has OH, C-H, C-O and C=C bonds. The bonds of OH and C-O indicated that the treatment was produced polar activated charcoal. The porous texture was influenced by H3PO4 concentration. The porous with dimension <5 >μ being predominant at low concentration of H3PO4 (0% and 5%) but larger amount of H3PO4 (10%) produced wide pore with dimension >5 μ.